2018
DOI: 10.1177/0003319718799589
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Postoperative Neutrophil–Lymphocyte Ratio and 6-Month Primary Patency of Percutaneous Transluminal Angioplasty in Femoropopliteal disease With Drug-Coated and Uncoated Balloons

Abstract: We investigated the relationship of postoperative neutrophil-lymphocyte ratio (NLR) with 6-month primary patency of percutaneous transluminal angioplasty (PTA) in femoropopliteal disease using drug-coated balloon (DCB) or uncoated balloon (UCB). This retrospective study included 106 patients who received DCB (n = 44) or UCB (n = 62). The postoperative NLR was lower in the DCB group than that in the UCB group (2.60 vs 3.23; P = .004), and 6-month primary patency rate was significantly higher in DCB group than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
(39 reference statements)
2
9
1
Order By: Relevance
“…Li et al [30] concluded that higher pre-NLR and pre-PLR levels were independent risk factors for the development of in-stent restenosis in patients who underwent drug-eluting stent implantation for coronary chronic total occlusion lesions. However, in the study, pre-NLR was not an independent predictor of PP at 6 months, which is in accordance with our previous report [16]. Larger samples are still needed to confirm our conclusion in the future.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Li et al [30] concluded that higher pre-NLR and pre-PLR levels were independent risk factors for the development of in-stent restenosis in patients who underwent drug-eluting stent implantation for coronary chronic total occlusion lesions. However, in the study, pre-NLR was not an independent predictor of PP at 6 months, which is in accordance with our previous report [16]. Larger samples are still needed to confirm our conclusion in the future.…”
Section: Discussionsupporting
confidence: 91%
“…Pre-dilatation with uncoated balloon was conducted conventionally before DCB. The DCB used in this study was coated with paclitaxel at 3 μg/mm 2 , and the method of use was as described previously [16].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, NLR after femoropopliteal PTA without stent implantation was shown to be significantly lower in patients treated with a drug-coated balloon (DCB) compared to patients treated with PTA with a uncoated balloon. Moreover, it was associated with a significantly higher primary patency rate after six months [78].…”
Section: Inflammatory Cellsmentioning
confidence: 92%
“…Similarly, target lesion patency or restenosis after DCB has also received increasing attention from clinicians. In a retrospective study ( 18 ), Zhen et al found that the 6-month target lesion patency rate (6-month primary patency) after DCB treatment for femoropopliteal artery disease was 77.3%, while the 6-month target lesion patency after uncoated balloon (UCB) treatment was only 53.2% ( P = 0.011). The definition of patency in the previous study is <50% lumen stenosis and the ratio of peak systolic velocity >2.4, which is consistent with the definition of restenosis in this study ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study with long-term follow-up, the results showed that femoropopliteal artery lesions with different TASC II classifications had different patency rates at 5-year postoperative follow-up after endovascular therapy, with type D lesions generally having the lowest rate of only 34% ( 17 ). A certain percentage of patients developed target lesion restenosis after DCB treatment of the femoropopliteal artery ( 18 , 19 ), and studies even found that DCB treatment of femoropopliteal artery disease increases the risk of death in patients ( 20 ). Therefore, screening the predictive factors of restenosis after DCB treatment for femoropopliteal artery disease has important clinical significance.…”
Section: Introductionmentioning
confidence: 99%